1971
DOI: 10.1177/030098587100800206
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Experimental Bovine Mycotic Placentitis Produced by Aspergillus fumigatus

Abstract: Eleven heifers were inoculated intravenously with a suspension of 1 x lo8 conidia of Aspergillus fumigatus at 169 or 170 days after artificial insemination. These principals were killed at 4, 7, or 14 days after inoculation or thereafter when abortion occurred. Four other heifers served as controls. Mycotic placentitis was not found at 4 days after inoculation. In principals killed at 7 and 14 days, 24% of placentomes had lesions of mycotic placentitis. Heifers that aborted had necrotizing lesions in approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
4

Year Published

1973
1973
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
2
16
0
4
Order By: Relevance
“…The placenta seems to be the only organ which provides a suitable environment for rapid vegetative growth of A . fumigatus (Hill et al, 1971) and we have demonstrated that placental extracts stimulate germination of A . fumigatus spores in vitro.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The placenta seems to be the only organ which provides a suitable environment for rapid vegetative growth of A . fumigatus (Hill et al, 1971) and we have demonstrated that placental extracts stimulate germination of A . fumigatus spores in vitro.…”
Section: Discussionmentioning
confidence: 81%
“…However, spores probably reach the placenta via the maternal blood since intravenous inoculation is the only successful method of experimental infection (Gilman and Birch, 1925;Bendixen and Plum, 1929;Hillman and McEntee, 1969;Hill et al, 1971). The placenta seems to be the only organ which provides a suitable environment for rapid vegetative growth of A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle, fungi gain entrance through the digestive tract and the infection is carried to the placenta by the blood [3].…”
Section: Sow I Iimentioning
confidence: 99%
“…from the mesenteric lymph-nodes of healthy cattle is important in that these organisms have been shown to infect other organs, including the placenta. Experimental infection of cattle with organisms of either genus can result in the development of asteroid bodies in the placenta (Dawson, unpublished observations;Hill et al, 1971). The recent literature on mycotic abortion, reviewed by Campbell (1969), emphasises the gaps in our knowledge of pathogenesis, and there appears to be no direct evidence that the spores of fungi commonly implicated in systemic mycoses such as mycotic abortion pass directly from the gut into the circulation.…”
Section: Alimentary Mycotic Lesions In Cattle 21mentioning
confidence: 99%